Development, reliability and validity testing of the Supportive Care Needs Scale for Patients with Bladder Cancer Undergoing Urostomy - GUO Can; CAO Ying; TANG Liping; YI Huarong; YI Jiqun; MEI Ziwei; Cai Shiying; XU Shuangying (Yixue xinzhi zazhi)
Objective To develop a Supportive Care Needs Scale for Patients with Bladder Cancer Undergoing Urostomy, and to test its reliability and validity.Methods Using the theory of supportive care needs as the theoretical framework, a predictive scale was developed by combining literature review, interviews, and Delphi method. A reliability and validity test was conducted on 189 patients with urinary stoma who visited a tertiary hospital in Nanchang, Jiangxi province from October 2022 to June 2023.Results The scale consists of 6 dimensions and 29 items. Exploratory factor analysis extracted 6 common factors, including psychological support needs, physical care needs, social support needs, disease treatment information support needs, professional medical support needs, and care skill knowledge support needs. The cumulative variance contribution rate of the factors was 70.221%. The content validity index at the item level was 0.78-1.00, S-CVI/Ave was 0.95, the total Cronbach's α coefficient of the scale was 0.909.Conclusion The Supportive Care Needs Scale for Patients with Bladder Cancer Undergoing Urostomy has good reliability and validity, and can serve as an effective assessment tool for measuring the supportive care needs of patients.